Itk derived signals regulate the expression of Th-POK and controls the development of CD4 T cells. - Jianfang Hu; Qian Qi; Avery August (PLoS ONE)
T cell development is critically dependent on both the environment and signals delivered by the T cell Receptor (TCR). The Tec family kinase Itk has been suggested to be an amplifier of signals emanating from the TCR and the loss of Itk partially affects most stages of thymopoiesis. Loss of Itk also differentially affects the development of conventional vs. non-conventional or innate memory phenotype T cells. Here, we examine whether these lineage choices are affected by a combination of TCR affinity and Itk by analyzing mice lacking Itk and carrying two TCR transgenes with differing affinities, OT-II and DO11.10. Our results show that developing thymocytes receive a gradient of signals, DO11.10>OT-II>DO11.10/Itk(-/-)>OT-II/Itk(-/-). We also show that the development of CD4(+) T cells is controlled by TCR signaling via Itk, which regulates the expression of the transcription factor, Th-POK, an enforcement factor for CD4 commitment. This results in a reduction in CD4(+) T cell development, and an increase in the development of MHC class II restricted TCR transgenic CD8(+) T cells that resemble non-conventional or innate memory phenotype CD8 T cells. This alteration accompanies increased expression of Runx3 and its target genes Eomesodermin, Granzyme B and Perforin in Itk null OT-II CD4(+) thymocytes. All together, these data suggest that Itk plays an important role in CD4/CD8 commitment by regulating signal thresholds for the lineage commitment. Our data also suggest that the lower level of TCR signaling that occurs with a low affinity TCR in the absence of Itk can redirect some MHC class II restricted CD4(+) T cell to class II-restricted CD8(+) innate memory phenotype T cells.